Predicting the deposition geometry and welding parameter of flux core arc welding for welding bead on plate with 1G position - Abdul Razak, Mohd Faizal (2017)
Flux Core Arc Welding (FCAW) is a popular choice for metal fabrication. The process of FCAW used semi-automatic setup and consumable electrode (flux in the core of consumable wire), which can generate shielding gas to protect weld pool from atmosphere during welding. The most critical factor that determine the welding output is the correct choice of welding parameters. The quality of welding is considered acceptable when bead geometry or profile has the right sizes and has minimum defects. To determine the quality of the welding, the visually and the macrostructure characterization can be carried out. The welding operator in industry gets the size of bead geometry and the welding parameters by trial and error. This approach is costly, including the wastage of materials, powers and the labour costs. Research findings published so far were only valid for small sample sizes and involved tedious analysis in order to predict the bead geometry and welding parameter, except the bead geometryheat input correlation method. In this work, large number of welded specimens were produced by Robotic FCAW process in 1G position. Only the bead geometry with good quality of samples were measured and tabulated. The heat input and weld bead geometry are plotted and the correlations of element of bead geometry were represented by the respective trend-line equations. These equations are used to predict the weld bead geometry and the welding parameters. The accuracy of the weld bead geometry was improved by grouping the data concerning the level of bead penetration that were collected from several experiments. The accuracy of prediction on bead geometry and welding parameters was found to be excellent, for more than 100 samples. The maximum deviation and the mean average deviation from experimental samples is less than 1mm.